2014
DOI: 10.1155/2014/616025
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor Alpha Confers Methotrexate Resistance via Attenuation of Reactive Oxygen Species Production and P53 Mediated Apoptosis in Osteosarcoma Cells

Abstract: Osteosarcoma (OS) is a malignant tumor mainly occurring in children and adolescents. Methotrexate (MTX), a chemotherapy agent, is widely used in treating OS. However, treatment failures are common due to acquired chemoresistance, for which the underlying molecular mechanisms are still unclear. In this study, we report that overexpression of estrogen-related receptor alpha (ERRα), an orphan nuclear receptor, promoted cell survival and blocked MTX-induced cell death in U2OS cells. We showed that MTX induced ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Cancer cells demonstrate high proliferating capabilities and require constant biosynthesis of macromolecules as building blocks for the generation of new cells, thereby resulting in a high-energy demand for cancer cells (14). ERRα demonstrates key regulatory roles in a variety of malignant processes, including proliferation, invasion, metastasis and chemotherapy resistance (15)(16)(17). Since ERRα serves a crucial role in cancer initiation, development and progression, it may be speculated that ERRα holds significant clinical significance for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells demonstrate high proliferating capabilities and require constant biosynthesis of macromolecules as building blocks for the generation of new cells, thereby resulting in a high-energy demand for cancer cells (14). ERRα demonstrates key regulatory roles in a variety of malignant processes, including proliferation, invasion, metastasis and chemotherapy resistance (15)(16)(17). Since ERRα serves a crucial role in cancer initiation, development and progression, it may be speculated that ERRα holds significant clinical significance for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our results confirmed the study that the expression of ERRa is correlated with osteosarcoma progression. 6 Considering that ERRa can activate Snail via both transcriptional and posttranscriptional mechanisms, 16 whether ERRa can regulate the stability of Snail protein also needs further studies in osteosarcoma cells.…”
Section: Erra Is Involved In Tfg-b Induced Transcription Of Snail In mentioning
confidence: 99%
“…4 Further, it can confer methotrexate resistance via attenuation of reactive oxygen species (ROS) production in OS cells. 6 However, the roles of ERRa in OS progression and whether it is related to EMT process are still not studied.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-18a was negatively correlated with ESRα expression in pre-eclampsia, which suggests that miR-18a is involved in the pathogenesis of pre-eclampsia, via negative regulation of ESRα expression (8)(9)(10)(11)(12)(13). Recent studies have shown that ESRα expression is involved in cell apoptosis (23), and that a change in cell apoptosis is associated with the pathogenesis of pre-eclampsia (24). Therefore, the low expression of miR-18a may affect trophoblast cell apoptosis by regulating ESRα expression, which may contribute to pre-eclampsia.…”
Section: Suppression Of Mir-18a Expression Leads To Decreased Cell Inmentioning
confidence: 99%